The Impact of EU Law on Consumer Protection in Real Estate Development Contracts (Pre-construction Contracts) - Lic, Jan (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The real estate development contract is partially regulated in the Act on the protection of the purchaser of dwelling premises or a detached house. This Act provides for three types of consumer protection measures: those related to the protection of the purchaser’s interest at the moment of concluding the contract, those that secure his payments and those related to the stage of implementing the commitments of the developer. Moreover, the Act provides for civil penalties and criminal sanctions in respect of the developer’s obligations. The impact of EU law on this Act is not unambiguous. On the one hand, EU legislation indicates and supports the overall objective of the regulation, namely the protection of the consumer. On the other hand, there is no corresponding directive on consumer protection in the real estate development contracts. Unfortunately, the European Union has not exercised the power granted to it under articles 4 and 169 of the Treaty on the Functioning of the European Union. It is only in the area of the liability for defects of the subject matter of a contract that one can perceive the direct impact of EU law, because in this respect Directive 1999/44/EC applies within the EU.